Developing Children's Self-Control Based on Islamic Values to Prevent the Negative Impacts of Digital Device Usage - Erhamwilda, Erhamwilda; Afrianti, Nurul; Hayati, Fitroh (MIMBAR : Jurnal Sosial dan Pembangunan, 2024)
Self-control is a critical skill essential for children to navigate the challenges posed by digital devices effectively. This study explores the role of Islamic values in fostering children's self- control to mitigate the negative consequences of modern digital interactions. The research involves a comprehensive literature review encompassing child development theories, Islamic teachings, and the implications of digital technology on young minds. Children's use of digital devices is a certainty for interacting with the online world. The internet offers various benefits but also brings several challenges and risks, especially for children and adolescents who lack strong self-control. Islamic teachings contain commands to develop self-control, which involves restraining oneself from actions prohibited by Allah and striving to follow Allah's commands. This study seeks to answer the following questions: 1) How is the process of developing children's self- control? 2) How is self-control developed according to Islamic guidance? 3) What are the negative impacts of digital device usage on children? A qualitative approach with literature review methods is used in this study. The results show that: 1) Self-control can be fostered through modeling, reinforcement, cognitive-behavioral techniques, delaying gratification, setting clear and consistent expectations and rules, etc.; 2) Parents need to guard their children's sight, hearing, and heart early through digital parenting. Parents play a crucial role in developing their children's conscience and preventing exposure to films, stories, games, and information that could damage their children's faith and morals. In conclusion, integrating Islamic values into children's education regarding self-control offers a holistic approach to safeguarding their well-being amidst the pervasive influence of digital devices. This approach not only supports their moral development but also prepares them to navigate the digital world responsibly and ethically.